Philosophical Sufism: An Analysis of Suhrawardi’s Contribution with Special Reference to His School of Illumination (Ishraqi) - Obaidullah, Muhammad (Afkar: Jurnal Akidah dan Pemikiran Islam, 2015)
Present study aims at asserting the philosophical mysticism of Shihab al-Din Yahya Suhrawardi (1154-1191 A.D.), the philosopher-mystic and the founder of the School of Illumination (Ishraqi), who is universally known as Shaykh al-Ishraqi. This paper also highlights the origin of the theory of Illumination (Ishraqi), its’ nature and role towards the philosophical sufi’s thought. Additionally, it concludes with stating the influential necessity of this doctrine in the present world to revive and purify our soul to accomplish the success in this life and hereafter with the critical evaluation of others. The methodologies applied in the study are critical and analytical.